2022
DOI: 10.3390/app12052365
|View full text |Cite
|
Sign up to set email alerts
|

Sous Vide Cooking Effects on Physicochemical, Microbiological and Sensory Characteristics of Pork Loin

Abstract: Pork loin slices were sous vide cooked at 60 °C and 65 °C for 2 h, 3 h and 4 h, and at 70 °C and 75 °C for 1 h, 1.5 h and 2 h. The cooking loss of the meat samples significantly increased with the temperature and time of heat treatment, but no correlation between cooking loss and moisture content in the samples was noted. All samples showed similar pH and water activity values. Regarding colour parameters, only yellowness showed significant differences between the samples and was affected by the temperature an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 51 publications
0
23
0
2
Order By: Relevance
“…Not only temperature but the cooking time also had a significant effect on these 2 parameters. In the work of Kurp et al (2022) , the moisture content in raw pork meat was 72.45%, and as a result of cooking (60, and 65°C/2, 3, 4h, also 70, and 75°C/1, 1.5, 2h), it declined significantly to 62.32-68.91%. Meat cooked at 60°C for 2h showed the highest moisture retention.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Not only temperature but the cooking time also had a significant effect on these 2 parameters. In the work of Kurp et al (2022) , the moisture content in raw pork meat was 72.45%, and as a result of cooking (60, and 65°C/2, 3, 4h, also 70, and 75°C/1, 1.5, 2h), it declined significantly to 62.32-68.91%. Meat cooked at 60°C for 2h showed the highest moisture retention.…”
Section: Resultsmentioning
confidence: 96%
“…Also, Becker et al (2015) confirmed the results of Christensen et al (2011) , that temperature was the main factor affecting cooking loss at low temperatures (53, and 58°C), and long time (10, 20, and 30h) treated pork meat while holding time had a smaller impact. In an experiment of Kurp et al (2022) with pork meat subjected to sous-vide with different combinations of temperature (60, 65, 70, 75°C) and time (1, 1.5, 2, 3, 4h) it was observed the cooking loss was in the range from 18.16 to 36.66%, and it increased significantly with temperature and cooking time. The interaction of temperature and cooking time also showed a significant effect on cooking loss.…”
Section: Resultsmentioning
confidence: 99%
“…OMb is deoxygenated to an unstable form, DMb, under low oxygen levels. The ferrous Mbs, namely OMb and DMb, are mainly oxidized to ferric Mb or MMb by enzymes and spoilage bacteria during storage rather than heating [ 42 ]. MMb forms the brown globin hemichromogen or ferrihemochrome when the globin is heat-denatured.…”
Section: Resultsmentioning
confidence: 99%
“…OMb and MMb are denatured to the red globin hemochromogen, also known as ferrohemochrome, which is then readily oxidized to brown ferrohemochrome, the pigment that imparts a dull-brown color to cooked meat [ 41 ]. Therefore, protein denaturation increases during heating, resulting in higher brightness and lower redness of meat products [ 42 ]. However, in this study, the absence of oxidation due to the lack of oxygen reduced the formation of OMb and DMb and reduced the extensive Maillard reactions, resulting in the least browning in the V99 group [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Each sample of pork loin was prepared and cut into dimensions of 2×9×5 cm (length×width×height) with an average weight of 81.99±2.33 g (n=36) and vacuum-packed in a vacuum packaging machine (C 15-HL, Webomatic). Sous vide of pork loin was carried out using the method described by Kurp et al (2022) . The vacuum-packed pork loin samples were cooked in a water bath (JSWB-30T, JSR, Gongju, Korea) set at 65°C for 2 h, i.e., until the core temperature reached 65°C.…”
Section: Methodsmentioning
confidence: 99%